Re-examination of the criteria for clinical evaluation on bacterial prostatitis--analysis of the data of the clinical study of temafloxacin - Arakawa, S (Hinyokika kiyo. Acta urologica Japonica, 1994)
The clinical efficacy of temafloxacin (TMFX) was evaluated in the patients with acute prostatitis (AP: 31 cases) and chronic prostatitis (CP: 75 cases), and the criteria for clinical evaluation on bacterial prostatitis by the Japanese UTI Committee were re-examined. The clinical efficacy of TMFX on prostatitis was examined. The number of the evaluable cases by doctors in charge were 30 and 68 for AP and CP, respectively. The efficacy rates were as high as 96.7% for AP and 80.9% for CP. In the patients whose efficacy could be evaluated by the Committee, the efficacy rates were as high as 100% (15/15) for acute bacterial prostatitis (ABP) and 66.7% (18/27) for chronic bacterial prostatitis (CBP). The bacteriological eradication rates were 100% (15/15) for ABP and 81.5% (22/27) for CBP. Adverse drug reactions were observed in 8 of 100 cases (total evaluable cases) but they clinically did not consist any problems. Abnormal laboratory test findings were observed in 9 of 71 cases (total evaluable cases), whose changes were all slight and did not clinically cause any problem. Therefore, TMFX was concluded to be highly useful in the treatment of ABP and CBP. The criteria for clinical evaluation on bacterial prostatitis were re-examined. Concerning the treatment period, comparison of the evaluation at Day 7 with that at Day 14 in ABP revealed that the efficacy was evaluable at Day 7. In the same way, comparison of the evaluation at Day 14 with that at Day 28 in CBP revealed that the efficacy was evaluable at Day 14. Concerning the pathogens, in ABP, the major pathogens were considered to be GNR as well as E. coli. On the other hand, in CBP, GNR and E. faecalis, that were generally authorized to be pathogens, were detected in less than half of the patients, and CNS were detected in the other patients. Among the CNS cases, there were some cases that showed no relationship between improvement of clinical symptoms and bacterial response. Therefore, it is necessary to perform further studies on this matter. In conclusion, regarding the criteria for clinical evaluation on bacterial prostatitis proposed by the Japanese UTI committee, the treatment period for evaluation of efficacy was appropriate, and it is necessary to perform further studies in order to determine the pathogens in bacterial prostatitis